EVALUATION OF JOINT VENTURES IN PROPERTY DEVELOPMENT IN LAGOS, NIGERIA - Joseph Oyewale, Oyedeji, (Journal of Surveying, Construction and Property, 2020)
Joint venture is a new financing model adopted in property development. However, there is little or no research in evaluating the model which this study aimed at achieving. The study populations are the members of Real Estate Developers Association of Nigeria in Lagos. Data were gathered through structured questionnaires administered to the study population. Gathered data were presented and analyzed through tables, chats and likert scales. Findings from the study revealed that residential property is the class of property mostly developed through joint venture in the study area. Also, the most prevalent parties that go into a joint venture agreement in the study area are; private property developer and financial institutions and the least prevalent are private property developers and the government. Financing is the most important term in a joint venture agreement in the study area and the least important term is acquisition of equipment. Finally, financing is the most prevalent problem of joint venture in the study area and breach of joint venture agreement is the least. Recommendations were made on how to solve joint ventures problems in property development. Also, there is need for further research on the nature of relationship between parties going into joint ventures.